Euplocania (Psocodea: Ptiloneuridae) in Peru, description of six new species - González-Obando, Ranulfo; Carrejo-Gironza, Nancy (Zootaxa, 2023)
Based on a review of specimens from Peru, six new species of the Euplocania (Ptiloneuridae) were found and assigned to species groups. The new species, here described and illustrated are: Euplocania alfonnerii n. sp., E. amarui n. sp., E. garcialdretei n. sp., E. katarii n. sp., E. matsiguenka n. sp. and E. wchipere n. sp. An identification key for Euplocania from Peru is included.